Documenting Traditional Forest-Related Knowledge of Medicinal Plants in Malaysia: A Comprehensive Approach (Journal of Tropical Resources and Sustainable Science (JTRSS), 2015)
Before United Nations Convention on Biodiversity (CBD) 1993, documentation of traditional forest related knowledge on medicinal plants did not consider much the issue of sustainable development and sharing of benefits with knowledge holders. While some academicians obtained their higher degrees from research on local knowledge, the indigenous and local communities providing the knowledge gained little. With the signing of CBD, countries have taken efforts to document the traditional knowledge to achieve CBD’s triple objective on conserving biological diversity, using natural resources sustainably and fairly and equitably sharing benefits deriving from the use of genetic resources. As a party to CBD, Malaysian government implemented a traditional knowledge (TK) documentation project on medicinal and aromatic plants of the aborigines (Orang Asli) in Peninsular Malaysia since 2007. In line with CBD and Malaysia’s National Policy on Biological Diversity (1998), the process of TK documentation among 15 Orang Asli sub-ethnic groups involved a comprehensive approach. A wide range of activities were carried out, namely conducting rapid rural appraisal, holding workshop on awareness raising, obtaining prior informed consent, carrying out socio-economic household survey, capacity building on documentation among the Orang Asli communities, database development, lab analysis of selected potential medicinal plants, developing prototype products and development of benefit sharing mechanism. Malaysia’s comprehensive model of TK documentation has attracted national and world attention. In 2013-2014, FRIM receives funding to conduct TK related R&D and training projects from (a) the Ministry of Agriculture (RM5.56 million), (b) international Islamic Development Bank (US$30,000), (c) United Nations Development Program and Global Environment Fund (US$533,000), and (d) Asia Pacific Association of Forestry Research Institutions (APAFRI) (US$1,500).
Keywords: Forest; traditional knowledge; medicinal plants; documentation